Effects of Three Preseason Training Programs on Speed, Change-of-Direction, and Endurance in Recreationally Trained Soccer Players - Koral, Jérôme; Lloria Varella, Jaume; Lazaro Romero, Fernando; Foschia, Clément (Frontiers in Physiology, 2021)
Background: Modern coaches experience a drastic reduction of the available training time with an increasingly large number of competitions during the competitive season. Thus, they must choose wisely the most efficient methods to improve the physical fitness of their players during the preseason. Among all the methods, this study compared the effects of plyometric training (PT), sprint interval training (SIT), and small-sided games (SSGs) on the performance of recreationally trained soccer players. Methods: Seventy-three participants were randomly assigned in one of the three experimental groups (i.e., PT [n = 23], SIT [n = 26] or SSGs [n = 24]) and completed two sessions per week for a total of 3 weeks. Meanwhile, the whole group maintained their habitual soccer-specific training program who do not interfere in the preparation of the season. Repeated sprint ability (RSA), maximal aerobic speed (MAS), and a 30-m sprint were assessed at baseline (PRE) and post-training (POST). Results: Performance in SSGs decreased for the average speed from 0 to 10 m (V0−10m; −0.84 km h−1, −4 ± 5%, p < 0.001), the maximal distance (Dmax) covered in the 30-s RSA test (−3.65 m, −3 ± 6%, p < 0.01) and MAS (−0.52 km h−1, −3 ± 6%, p < 0.01). PT increased the mean distance (Dmean) covered in the 30-s RSA test (+5.98 m, 5 ± 4%, p < 0.001) and MAS (+0.58 km h−1, 7 ± 5%, p < 0.01) while an improvement of all parameters but the maximal sprint speed reached during the 30-m trip (Vmax) was found in the SIT group (V0−10m: +1.462 km h−1, 8 ± 5%, p < 0.001; Dmax: +7.89 m, 6 ± 5%, p < 0.001; Dmean: +8.69 m, 7 ± 5%, p < 0.001 and MAS: +1.74 km h−1, 12 ± 8%, p < 0.001). All SSG POST values were significantly lower than PT and SIT (p < 0.01). Dmean and MAS in POST were also significantly higher in SIT than in the PT group (p < 0.001). Conclusion: This study suggests that both PT and SIT could be a better alternative to SSGs to boost performances during preseason. Moreover, SIT seems to produce higher improvements in physical performances than PT.